2019
DOI: 10.1186/s40834-018-0082-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service knowledge, perception, and use of emergency contraception among future healthcare providers in northern Ghana

Abstract: BackgroundEmergency contraception, if used properly, can prevent up to over 95 % of unwanted and mistimed pregnancies. However, a number of obstacle including healthcare providers knowledge, perception, and attitude towards emergency contraception (EC) prevent women and adolescents from having access to EC.MethodsThis was a cross-sectional study among 191 female final year nursing and midwifery students of Tamale Nurses and Midwives Training College in the Northern Region of Ghana. Purposive sampling method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 6 publications
7
26
3
Order By: Relevance
“…With level of education, the study revealed that young women with secondary/higher level of education had higher odds of unmet need for contraception compared with those with no formal education. This is similar to what Solanke et al [ 45 ] found in Nigeria and Guure et al [ 23 ] in Ghana. We admit just as Solanke et al [ 45 ] admitted in their study that this finding seem to be counter intuitive.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…With level of education, the study revealed that young women with secondary/higher level of education had higher odds of unmet need for contraception compared with those with no formal education. This is similar to what Solanke et al [ 45 ] found in Nigeria and Guure et al [ 23 ] in Ghana. We admit just as Solanke et al [ 45 ] admitted in their study that this finding seem to be counter intuitive.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to what Solanke et al [ 45 ] found in Nigeria and Guure et al [ 23 ] in Ghana. We admit just as Solanke et al [ 45 ] admitted in their study that this finding seem to be counter intuitive. The possible reason accounting for this finding might be that young women who have attained higher level of education, have higher likelihood of postponing marriage or childbearing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A possible explanation for this might be that increased years of maternal education brings about improvement in ANC attendance, nutritional status, health-seeking behaviour and enhanced maternal experiences relative to pregnancy and childcare. Furthermore, increased years of maternal education may cause delay in sexual initiation or increase uptake of contraception to prevent pregnancy [40, 41]. This inadvertently could increase maternal age at first birth and decrease the likelihood of LBW associated with teenage pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…One study that could be used to exemplify this found that among future healthcare providers in Ghana, the knowledge about when to use Cu-IUDs for EC was poor, with some 55% not being able to pin-point the time-frame for insertion. Almost 40% considered the use of EC in general as morally wrong, and some 55% said EC use promotes promiscuity (64).…”
Section: Review-choice Of Relevant Publicationsmentioning
confidence: 99%